Criminology placements and work experience opportunities in youth justice - Creaney, Sean (Knowledge and skills partnerships in youth justice, 2025)
This chapter will cover the what, why, and how of criminology placements and work experience opportunities in youth justice. A principal aim of the knowledge and skills partnership between Edge Hill University, the University of Chester and Cheshire Youth Justice Services is to craft and nurture fruitful opportunities for research and placement opportunities for undergraduate students. Work placements created through the partnership scheme provide valuable opportunities to advance employability skills, helping them to understand the steps required to enter a career in youth justice. This chapter presents insights into the types of practice and research placement opportunities available as part of the Building Professional Skills for Youth Justice (BPSYJ) programme. Conversations with students and alumni have been integrated within the chapter to illustrate the points. ‘Student as Producer’ is also part of the discourse and practice of the partnership arrangement. It is utilised as a guiding principle and applied into practice through work-based learning activities. This has involved viewing students not as passive recipients but as co-creators of knowledge and education. They are active agents, capable of engaging in a reflective scholarship and critical thinking through questioning orthodoxy or challenging the status quo. It is necessary to respect students as equal partners and aim to share power equally through democratising decision-making processes with students and forging collaborative relationships. Within this chapter, the ‘in focus’ case studies presented provide an in-depth illustrative account of how students have been involved directly in the learning process. This section of the chapter is particularly novel, presenting fresh insights into the theory-practice nexus from a unique standpoint (a student perspective!). The BPSYJ programme is principled and progressive. Practitioners working within the youth justice service have provided enriching experiences alongside substantial resource (non-monetary) contributions and built meaningful and supportive professional relationships with students and tutors alike. In providing a credible and persuasive account of the power of work-based learning, this chapter may help to pave the way for other youth offending team/university collaborations in the future to enrich the experiences of students with an interest in youth justice practice. Furthermore, some of the themes presented here may be of relevance to other professions and disciplines, especially interested parties who are jostling with ideas to secure work experience or mobilise research placements for students or bolster forms of critical thinking and reflective practices.